1979
DOI: 10.1111/j.1471-4159.1979.tb05180.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide‐galactosyltransferase and Cerebroside‐sulphotransferase Localisation in Golgi Membranes Isolated by a Continuous Sucrose Gradient of Mouse Brain Microsomes

Abstract: A 17,000 g supernatant of mouse brain microsomes was subfractionated on a continuous sucrose gradient in order to localise ceramide galactosyltransferase (CGalt, EC 2.4.1.47) and cerebroside sulphotransferase (CST, EC 2.8.2.1 l), both enzymes involved in the synthesis of myelin lipids. The submicrosomal fractions were analysed for marker enzymes of myelin, plasma membranes, Golgi membranes, endoplasmic reticulum and lysosomes, and their protein distribution was studied. The results and EM studies give evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…The finding that the ratio CMSP/cerebroside sulfates was identical to that of myelin suggested to us that the vesicular fraction could be constituted by "proto myelin" vesicles, a structure that was previously proposed to act as vector of some myelin components (Pasquini et al, 1987). Comparing the results obtained by us and those presented by Siegrist et al (1979), it can be observed that in the membrane fractions obtained with the continuous density gradient the activities of aryl sulfatase A, 2' ,3'-cyclic nucleotide 3'-phosphohydrolase, and 5'-nucleotidase along the gradient are distributed in a similar fashion. The distribution of thiamine pyrophosphatase, which was used in this work as marker of Golgi vesicles, differs from that of cerebroside sulfotransferase, which was used for similar purposes by Siegrist et al (1979).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The finding that the ratio CMSP/cerebroside sulfates was identical to that of myelin suggested to us that the vesicular fraction could be constituted by "proto myelin" vesicles, a structure that was previously proposed to act as vector of some myelin components (Pasquini et al, 1987). Comparing the results obtained by us and those presented by Siegrist et al (1979), it can be observed that in the membrane fractions obtained with the continuous density gradient the activities of aryl sulfatase A, 2' ,3'-cyclic nucleotide 3'-phosphohydrolase, and 5'-nucleotidase along the gradient are distributed in a similar fashion. The distribution of thiamine pyrophosphatase, which was used in this work as marker of Golgi vesicles, differs from that of cerebroside sulfotransferase, which was used for similar purposes by Siegrist et al (1979).…”
Section: Discussionmentioning
confidence: 47%
“…The activity of succinate dehydrogenase, an enzyme used to detect mitochondria, was absent in all the tubes. Electron microscopic examination of the vesicular fraction showed that it was constituted by a population of unilamellar vesicles very similar to that described by Siegrist et al (1979) as fraction 14, probably containing lysosome-like structures. Table I shows the composition of the vesicular fraction in comparison with similar data obtained from purified myelin and from a microsomal fraction isolated from whole brain homogenate.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Because we showed here that CGalT is localized to the ER, the previously reported CGalT activity in Golgi fractions (13,21,23,45) must be accounted for by a different enzyme. We here found that the CGlcT-deficient cell mutant GM95 not only lacked the ability to synthesize GlcCer but also failed to synthesize GalCer under low UDP-Glc conditions in vitro.…”
Section: Discussionmentioning
confidence: 71%
“…Ceramide UDPgalactosyltransferase [CGT; 2-hydroxyacylsphingosine 1-,B-galactosyltransferase; UDPgalactose:2-(2-hydroxyacyl)sphingosine 1-f3-D-galactosyltransferase, EC 2.4.1.45] is the key enzyme in biosynthesis of cerebrosides (7) and catalyzes the transfer of galactose from UDPgalactose to ceramide (8). The enzyme is found in rat brain microsomes (9), Golgi-enriched fractions (10), and myelin (11). Numerous attempts have been made to isolate and purify this membrane-bound enzyme (12)(13)(14)(15).…”
mentioning
confidence: 99%